Diplodia tip blight pathogen’s virulence empowered through host switch - Blumenstein, Kathrin; Bußkamp, Johanna; Langer, Gitta Jutta; Terhonen, Eeva (Frontiers in Fungal Biology, 2022)
Increased drought combined with emerging pathogens poses an increased threat to forest health. This is attributable to the unpredictable behaviour of forest pathosystems, which can favour fungal pathogens over the host under persistent drought stress conditions. Diplodia sapinea (≡ Sphaeropsis sapinea) is one of the most severe pathogens in Scots pine (Pinus sylvestris) causing Diplodia tip blight (conifer blight) under certain environmental conditions. Recently, the fungus has also been isolated from non-conifer hosts, indicating that it has a broader host range than previously known. In this study we compared the impact of different levels of water availability on necrosis length caused by D. sapinea strains isolated as endophytes (eight strains isolated from asymptomatic Scots pine) and pathogens (five strains isolated from symptomatic Scots pine) and five strains isolated from symptomatic non-pine hosts. For all strains the decreased water availability increased the necrosis length in Scots pine shoots. The isolates from non-pine hosts caused the most severe reactions under all water availabilities. The results of the study indicate the likelihood that effects of climatic changes such as drought will drive D. sapinea damage in Scots pine-dominated forests and increase mortality rates in affected trees. Further, the higher necrosis in the Scots pines caused by strains that had performed a host switch are concerning with regard to future scenarios thus increasing infection pressure on Scots pine from unknown sources.